The relationship between the quality of work life and organizational commitment among staff in Hospital Machang,Kelantan / Siti Nornadia Zulkarnain - Zulkarnain, Siti Nornadia (2015)
This research was conducted to find out the relationship between the quality of work life and organizational commitment among staff in Hospital Machang, Kelantan. The objectives were identify the factors of quality of work life that influences the organizational commitment, to identify the most contributing factors of quality of work life that influence organizational commitment and to investigate whether there is any relationship between the quality of work life and organizational commitment among staff in Hospital Machang, Kelantan. Correlation research was used and questionnaire was used as researh instrument. The sample population of 180 staffs was taken and the respondents were stratified based on 13 departments in the Hospital Machang, Kelantan. This results show the factors of quality of work life that influences the organizational commitment among staff in Hospital Machang, Kelantan were career development or reward system.